Discovery of hundreds of mirtrons in mouse and human small RNA data - Ladewig, Erik; Okamura, Katsutomo; Flynt, Alex S.; Westholm, Jakub O.; Lai, Eric C.

(untitled) (Genome Research, 2012)
Atypical miRNA substrates do not fit criteria often used to annotate canonical miRNAs, and can escape the notice of miRNA genefinders. Recent analyses expanded the catalogs of invertebrate splicing-derived miRNAs (“mirtrons”), but only a few tens of mammalian mirtrons have been recognized to date. We performed meta-analysis of 737 mouse and human small RNA data sets comprising 2.83 billion raw reads. Using strict and conservative criteria, we provide confident annotation for 237 mouse and 240 human splicing-derived miRNAs, the vast majority of which are novel genes. These comprise three classes of splicing-derived miRNAs in mammals: conventional mirtrons, 5′-tailed mirtrons, and 3′-tailed mirtrons. In addition, we segregated several hundred additional human and mouse loci with candidate (and often compelling) evidence. Most of these loci arose relatively recently in their respective lineages. Nevertheless, some members in each of the three mirtron classes are conserved, indicating their incorporation into beneficial regulatory networks. We also provide the first Northern validation for mammalian mirtrons, and demonstrate Dicer-dependent association of mature miRNAs from all three classes of mirtrons with Ago2. The recognition of hundreds of mammalian mirtrons provides a new foundation for understanding the scope and evolutionary dynamics of Dicer substrates in mammals.